2000
DOI: 10.1046/j.1471-4159.2000.0750954.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Exposure Alters the Expression Pattern of Neural Cell Adhesion Molecules During Brain Development

Abstract: Neural cell adhesion molecules (NCAMs) play critical roles during development of the nervous system. The aim of this study is to investigate the possible effect of ethanol exposure on the pattern of expression and sialylation of NCAM isoforms during postnatal rat brain development because alterations in NCAM content and distribution have been associated with defects in cell migration, synapse formation, and memory consolidation, and deficits in these processes have been observed after in utero alcohol exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
53
0

Year Published

2002
2002
2011
2011

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(55 citation statements)
references
References 64 publications
2
53
0
Order By: Relevance
“…Indeed, ethanol decreases the production and release of growth factors and the intracellular and plasma membrane levels of the highly sialylated form of the neural cell adhesion molecule (PSA-NCAM) in astrocytes (Miñana et al 2000). However, these effects may be the synergic result of alterations in the glycosylation process and the cytoskeletal components that participate in the intracellular traffic.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, ethanol decreases the production and release of growth factors and the intracellular and plasma membrane levels of the highly sialylated form of the neural cell adhesion molecule (PSA-NCAM) in astrocytes (Miñana et al 2000). However, these effects may be the synergic result of alterations in the glycosylation process and the cytoskeletal components that participate in the intracellular traffic.…”
Section: Discussionmentioning
confidence: 99%
“…Incubation time was 60 min at 37°C. After two 10-min rinses in 0.1% BSA-Tris buffer and a rinse in redistilled water, the sections were air-dried and finally counterstained with uranyl acetate and lead citrate (Renau-Piqueras et al 1989;Miñana et al 2000). Quantitative analysis of gold particle distribution on Golgi apparatus areas was carried out using stereological methods (Renau-Piqueras et al 1987, 1997.…”
Section: Fluorescence Microscopymentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, optimal levels of neural cell adhesion molecules (eg, NCAM and L1) play an important role in stable synapse formation (Edelman and Chuong, 1982). It has been shown that perinatal ethanol exposure alters the pattern of NCAM and L1 expression, inhibiting the formation of new synapses (Minana et al, 2000;Bearer, 2001). Prenatal ethanol exposure reduces neuronal numbers (Perez et al, 1991) with less elaborate dendritic arbors, fewer dendritic spines (Smith and Davies, 1990;Abel et al, 1983;Ferrer et al, 1988;Perez et al, 1991), and decreased vesicle number per area of synaptic contact zones (Lolova et al, 1989) in the CA1 hippocampus.…”
Section: Therapeutic Effects Of Aniracetammentioning
confidence: 99%